Impact of environmental sustainability information and sustainable consumption measures on consumer willingness to pay - Kellner, Ann-Kathrin (2022)
The destructive impact of climate change and the significance of sustainable consumption as one mitigating factor emphasize the necessity of societal change for a viable future. This paper investigates sustainable consumption by contrasting consumers’ stated willingness to pay for hypothetical chocolate bars with varying environmental sustainability information. To elicit these values, an open-ended question format is employed, with the questionnaire collecting further consumer data. With the obtained sample of 209 participants, findings show that consumers are willing to pay significantly more for environmentally sustainable options. This increase is magnified once certified sustainability information is disclosed. The results further indicate that previously validated measures of general purchasing behavior, perceived consumer effectiveness, environmental attitude, and willingness to pay more for sustainable goods are significant determinants of the increase in willingness to pay. Additionally, education and income are significant factors, while gender did not prove to be relevant. This underlines the price premium placed on green goods and the need for companies to focus on sustainability.